Síntese derivados fenilpropanóicos - Borges, Flávio Valadares Pereira (2020)
Phenylpropanoids and their derivatives have been widely studied for their structural varieties and biological activities. This work reports the obtaining of esters of phenylpropanoic acids and monoterpenic alcohols, obtained through the reactions of Schotten-Bauman and WittigHorner, the obtaining of the neolignan dehydrodieugenol by oxidative coupling promoted by potassium ferrocyanide and peroxidase contained in coconut water, as well as the report of its leishimanicidal activities for the promastigote form of Leishmania amazonensis and the comparison between the techniques regarding stereo selectivity. The neolignan lycarin- (A) was obtained, with the coupling promoted by coconut water and variations were made in the order of addition of reagents and injection speed comparing the influence on yield, methyl lignan dehydrodicumarate was also synthesized, obtained through esterification Fischer and subsequent oxidative coupling. Four phenylethylamines and two indoletylamines cinamoylamides were also obtained, these being described for the first time in this work through the formation of acyl chloride with Vilsmeyer-Haack reagent and later SchottenBaumann reaction to form amide. The results of this work yielded three publications in pharmaceutical chemistry journals.